Elastase Deficiency Phenotype of Pseudomonas aeruginosa Canine Otitis Externa Isolates - Petermann, Shana R. (American Society for Microbiology, 2001)
Pseudomonas aeruginosa veterinary isolates were assayed for elastase and total matrix protease activity. The elastase activity of canine ear isolates was much less than that of strain PAO1 and that of all other veterinary isolates (P < 0.0001). The results indicate that canine ear isolates have a distinct elastase phenotype.